The Effects of Cold Pelleting and Separation of Fine Corn Particles on Growth Performance and Economic Return in Nursery Pigs - C. E. Evans; M. Saensukjaroenphon; C. K. Jones; J. M. DeRouchey; J. C. Woodworth; M. D. Tokach; C. B. Paulk; C. R. Stark (Kansas Agricultural Experiment Station Research Reports, 2017)
A total of 320 pigs (DNA 241 × 600; initially 22.5 lb BW) were used in a 21-d experiment to determine the effects on pelleting technique and removing fine corn particles (<150 microns) on nursery pig growth performance. There were 5 pigs per pen and 8 pens per treatment and diets were all manufactured using corn ground to 400 microns. Diets were fed as a mash or pelleted using a traditional vertical die pellet mill equipped with a steam conditioner (steam pellet) or a horizontal pellet die with hot water conditioning prior to pelleting (cold pellet). Therefore, the 8 treatments were: 1) ground corn diet fed as mash, 2) ground corn diet steam pelleted, 3) ground corn diet cold pelleted, 4) ground corn with fines less than 150 microns removed from the diet and the diet fed as mash, 5) ground corn with fines less than 150 microns removed from the diet and the diet without fines was steam pelleted, 6) ground corn with fines less than 150 microns removed from the diet and the diet without fines was cold pelleted, 7) fines less than 150 microns were steam pelleted then proportionally added back to ground corn and fed as a mixture of pellets and mash, and 8) fines less than 150 microns were cold pelleted then proportionally added back to ground corn and fed as a mixture of pellets and mash. Removal of fines less than 150 microns from the corn improved the flowability characteristics of the diets as indicated by improved composite flow index values. The best flowability was achieved when fines were pelleted and added back to the mash diets. Pigs fed steam- or cold-pelleted diets had decreased (P<0.02) ADG, ADFI, and d-21 BW, total feed cost, revenue, and income over feed cost (IOFC) compared to those fed mash diets. Pigs fed steam pelleted diets had decreased (P<0.006) ADG, d-21 BW, revenue, and IOFC compared to those fed cold pelleted diets. There were no growth performance differences between pigs fed ground corn diets or ground corn diets with fines removed. Pigs fed diets with fines removed, pelleted, and subsequently added back had increased (P<0.05) ADFI, F/G, and feed cost compared to all other treatments. It is assumed that this response resulted from increased feed wastage resulting from pigs sorting pellets mixed with mash diets. The results of this study indicate that removing particles less than 150 microns improved the flowability of a mash diet without sacrificing growth performance. Additionally, cold pelleting was a viable option to steam pelleting in the current experiment. However, pelleting diets reduced pig performance compared to pigs fed mash diets. Further research is needed to validate the response to cold pelleting when the expected response to pelleting using steam conditioning is achieved.
Keywords: pelleting; thermal processing; cold pelleting; particle size